Efficacy of Two Species of Coccinellid Predators Against Four Different Aphid Pest Species at Khumaltar, Nepal - Maharjan, B.; Thapa, R. B.; Bajracharya, A. S.R. (Journal of the Institute of Agriculture and Animal Science, 2018)
An experiment was conducted in completely randomized design (CRD) to study the efficacy and biology of two coccinellid species with four aphid species at the mass-rearing laboratory of Entomology Division, Nepal Agricultural Research Council (NARC), Khumaltar from February to May 2016. Two coccinellid species, i.e. Coccinella septumpunctata Linn. and Adonia variegate (Goeze) were given four aphid species viz; Myzus persicae (Sulzer), Lipaphis erysimi (Kaltenbach), Aphis craccivora (Koch) and Brevicorynae brassicae Linn. separately to compare the efficacy of two beetle species as effective bio-control agent. Predatory activity of C. septumpunctata was the highest on L. erysimi(feeding 183 aphids) and the lowest on A. craccivora (feeding on 126 aphids), while, that of A. variegate (Goeze) was the highest on L. erysimi (feeding 155.4 aphids) and the lowest on B. brassicae (feeding 112 aphids) during their larval stages. Fourth instar individual larval weight of C. septumpunctata was recorded the highest (26.82 mg) when fed on A. craccivora and the lowest (13.9 mg) when fed on B. brassicae, while the 4th instar larval weight of A. variegate was only 12.82 mg and 11.34mg when fed on same aphid species. Pupal and adult weight was also recorded the highest for C. septumpunctata as compared to A. variegata. Similar result was obtained for weights of adult when larvae fed on A. craccivora. The weight of female was observed relatively higher than that of male from this study for both beetle species. There was a positive correlation between predation and weight gained by larvae with respect to all aphid species. From this study, it can be concluded that C. septumpunctata seems better promising species of predators of aphids, especially beneficial in biological control of aphid species.